High-throughput generation of hyaluronic acid microgels via microfluidics-assisted enzymatic crosslinking and/or Diels–Alder click chemistry for cell encapsulation and delivery. (December 2017) - Ma, Ting; Gao, Xijie; Dong, Hua; He, Huimin; Cao, Xiaodong
Graphical abstract: Abstract: Cell encapsulation in 3D microgels offers unique advantages to meet the complicated requirements in tissue engineering, regenerative medicine and cell therapy. Herein we report high-throughput microfluidic generation of cell-laden microgels based on a new hyaluronic acid (HA) derivative, i.e. furylamine and tyramine grafted HA molecules, which can be crosslinked via either enzymatic crosslinking, or Diels–Alder click chemistry, or both. Compared with traditional photoinitiated free radical polymerization and Michael conjugate addition reaction, enzymatic crosslinking and click chemistry crosslinking show higher chemical selectivity and milder reaction conditions. More importantly, the switching of crosslinking strategy in the same molecule makes it possible to fabricate microgels with almost the same composition but variable gelation time and elasticity. Using ATDC-5 cells as model cells, three types of cell-laden microgels were generated in high-throughput manner and their potentials as cell carriers were evaluated in detail by comparing their mechanical elasticity, gelation time, microgel size, swelling ratio, cell viability, enzymatic degradation and bioactivity of released cells. Our results reveal that the new HA-derived microgels crosslinked by enzymatic crosslinking and Diels–Alder click chemistry are very promising candidate for cell encapsulation and delivery.